Analysis Accuracy of Diagnosis Codes and Procedure Code in JKN Patient Delivery Cases at RS X Special Region of Yogyakarta - Pradita, Riska; Widowati, Vidya; Reni Tahayu, Kavita; Mazaya Fitriana, Syarah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
One of the activities in accordance with PMIK competency is the classification and coding of diseases and actions. The provision of diagnosis and action codes refers to the ICD-10 and ICD-9-CM rules. According to WHO (2016), coding of childbirth cases consists of conditions or complications (O00-O99), method of delivery (O80-O84), and Outcome of delivery (Z37,-). In practice in health care facilities, there are still inaccuracies in diagnosis and action codes in childbirth cases because they are classified as complex codes. The purpose of this study was to determine the process of implementing diagnosis and action codes, the process of implementing claims and factors causing pending claims, the percentage of accuracy of diagnosis and action codes and factors causing inaccuracy of diagnosis and action codes in childbirth cases of JKN patients at RS X Bantul. The type of research uses qualitative descriptive research. With a sample of objects of 75 medical records of childbirth cases of JKN patients with a simple random sampling technique and a sample of subjects of 4 informants with a purposive sampling technique. Data collection by observation, document study and in-depth interviews with 4 informants. The data validation technique in this study used source triangulation and technique triangulation. The results showed that the coding process was carried out by looking at medical records and then inputting the code into the SIMRS. The claim implementation process was carried out cumulatively and submitted to BPJS every 7th or 8th. In the case of pending labor, claims were caused by code incompatibility between the hospital and BPJS. The percentage of accuracy of the complication component was 54.7% (41), method of delivery (46.7)% (35), and outcome of delivery 94.7% (71), and action 29.3% (22). In addition, the results of the inaccuracy of the complication component were 45.3% (34), method of delivery 53.3% (40), and outcome of delivery 5.3% (4), and action 70.7% (53). The factors causing inaccuracy of diagnosis codes and actions were influenced by human resources who verified the code did not meet the competence of medical recorders, and there was no special training for coding officers. There is no budget allocated specifically for the implementation of the codification process. There is already an SOP on coding but the written procedures are still incomplete. Inaccuracy of diagnosis and action codes in cases of JKN patient labor can cause delays in payments to the hospital.